Hepatitis C Virus: A Critical Appraisal of New Approaches to Therapy. (8th October 2012) - Nelson, David R.; Jensen, Donald M.; Sulkowski, Mark S.; Everson, Greg; Fried, Michael W.; Gordon, Stuart C.; Jacobson, Ira; Reau, Nancy S.; Sherman, Kenneth; Terrault, Nora; Thomas, David
Abstract : The HCV council 2011 convened 11 leading clinicians and researchers in hepatitis C virus from academic medical centers in the United States to provide a forum for the practical and comprehensive evaluation of current data regarding best practices for integrating new direct-acting antiviral agents into existing treatment paradigms. The council investigated 10 clinical practice statements related to HCV treatment that reflect key topical areas. Faculty members reviewed and discussed the data related to each statement, and voted on the nature of the evidence and their level of support for each statement. In this new era of DAAs, a comprehensive and critical analysis of the literature is needed to equip clinicians with the knowledge necessary to design, monitor, and modify treatment regimens in order to optimize patient outcomes.